The Education System in the Russian Federation : Education Brief 2012 - Nikolaev, Denis; Chugunov, Dmitry (Washington, DC: World Bank, 2012)
This study is intended for non-Russian researchers wanting to get familiar with the education system of the Russian Federation and more generally for all those involved in education and education policy. It does not represent exhaustive information on the Russian education system and all problems and challenges existing there, but briefly describes its main features. The report has the following structure. The opening chapter provides an overview of the education system in Russia and briefly reviews the most evident emergent trends. Chapters two through five are devoted to description of education system by level. The chapters are arranged by ascending order of educational level and each chapter's present information in a progression from the most general to the most specific. First, data on the current state of education system is provided. They characterize the human and financial resources allocated to education; describe the network of educational institutions across the country, and show regional disparities of spending on education. Next in each section key problems and challenges are examined; the focus is mainly made on access to and quality of educational services. Third, information on recent and ongoing reforms in the education sphere addresses each subsector separately and defines features typical for each of them. Fourth, there is discussion of policy options and analysis of what can be improved in the Russian education sphere. Finally, section six is devoted to lifelong learning. First, the section focuses on the condition of and development trends in lifelong learning. Then it examines the state of policy, staff training including financing and coverage, and learning for socially deprived groups of people. The section concludes with policy options and possible measures for improvement.